Study on the heating law of thermal effect of HIFU on tissue based on piezoelectric ceramic voltage and vibration frequency - Yuping Long; Yi Gan; Fujia Sun; Yansong Zhao (Scientific Reports, 2025)
Abstract When high-intensity focused ultrasound (HIFU) is used to heat human tissues during surgery, shortening the heating time and increasing the heating rate are crucial for implementing surgery. During operations, the vibration frequencies and voltages that are suitable for piezoelectric ceramics can maximize the heating rate of HIFU. To correctly select the frequency and voltage of piezoelectric ceramics, it is necessary to understand the change law between the frequency and voltage of piezoelectric ceramics and the temperature of the heated tissue. Therefore, this study focuses on the piezoelectric ceramics in the ultrasonic transducer that produces HIFU. By coupling the piezoelectric equation, Helmholtz equation, and biological heat transfer equation of piezoelectric ceramics, the solid mechanical properties of piezoelectric ceramics and the sound field and temperature field produced by its vibration are combined to determine the influence of vibration frequency and voltage on heating time. Results show that the relation between the temperature variation of the tissue, vibration frequency, and voltage of the piezoelectric ceramics can be determined using the Rational Taylor function. The maximum voltage that the piezoelectric ceramics with different frequencies can withstand varies greatly.